Incidence of various urothelial malignancy in patients undergoing transurethral resection of bladder tumour in tertiary care hospital - Kaur, Kamal Preet; Bhangu, Gurpreet Singh; Bansal, Darpan; Julka, Divya (International Surgery Journal, 2020)
Background: Urinary bladder lesions are a great health concern as it lies among the top ten most common cancers in the world. These range from benign, harmless lesions that do not recur to life threatening tumors. The present study was undertaken to study incidence of various urothelial cancer in patients undergoing transurethral resection of bladder tumor in tertiary care hospital, as the treatment, follow up and prognosis is highly variable with different subtypes of bladder cancer. Methods: A hospital based descriptive cross-sectional study was conducted on all patients undergoing transurethral resection of bladder tumor from December 2018 to May 2020 in the Department of General Surgery of Sri Guru Ramdas Institute of Medical Sciences and Research, Amritsar. Based on World Health Organization (WHO) classification incidence of various urothelial malignancy was calculated. Results: Out of 80 patients with growth urinary bladder, 4 patients (5% of total patient) were diagnosed as case of papilloma, 26 patients (32.5% of total patients) were diagnosed as low grade papillary urothelial carcinoma, 50 patients (62.5% of total patients) were of high grade papillary urothelial carcinoma. There were no case of PUNLMP in our study. Conclusions: It can be concluded that majority of the patient undergoing transurethral resection of bladder tumor are diagnosed with high grade papillary carcinoma.